Dry Ashing for Signal Enhancement in Laser-Induced Breakdown Spectroscopy (LIBS) - Lázaro, Maisa Cristina [UNESP] (2021)
Limited sensitivities of some laser-induced breakdown spectroscopy (LIBS) instruments may impair some applications. Although this drawback can be minimized by instrumental improvements, the complexity of operations and cost increases. In this work the principle of conventional dry ashing for sample preparation was evaluated as a simple and low-cost alternative to improve the sensitivity of LIBS analysis. Botanical, agronomic and industrial samples were analyzed. Samples were dry heated and their LIBS emission signals were evaluated. The results suggest the dry heating caused structural changes in samples providing greater availability of the analyte, which resulted in the enhancement of the signals. As proof of concept, the strategy was applied for Sr determination in plant leaves. Two Sr emission lines, enhanced after sample dry ashing were used. The developed methods showed similar performance featuring a good linear range (10 to 70 μg g−1) with coefficient of correlations higher than 0.99. Additionally, the accurate determination of Sr in apple and peach leaves standard materials was achieved.